CHARACTERIZATION OF XYLANASE FROM A XYLANOLYTIC- THERMOPHILIC BACTERIUM ISOLATED FROM GUNUNG PANCAR HOT SPRING, WEST JAVA - SUWANTO, ANTONIUS; SURYANTO, DWI; MERYANDINI, ANJA (SEAMEO BIOTROP, 2001)
A xylanolytic-thermophilic bacterium (IT-08) was isolated from Gunung Pancar Hot Spring after two days of enrichment in Modified Thermus Medium (MTM) supplemented with 0.5% oat spelt xylan. 16S-rRNA sequence analysis indicated that IT-08 resembles Bacillus thermoleovorans, a species of thermophilic bacteria. When grown on xylan containing media, IT-08 produces a thermoactive xylanase. Xylanase from IT-08 was active at temperatures between 40 and 100Â°C, at pH values between 4.0 and 9.0 with optimum values obtained at 80Â°C and pH 6.0, respectively. SDS-PAGE and zymogram analysis demonstrated that a crude xylanase complex of IT-08 comprised two active bands with molecular masses of 78 and 60 kDa. Keywords: xylanase / xylanolytic-thermophilic bacteria